Dual role of phenols as fragrances and antioxidants: mechanism, kinetics and drastic solvent effect. (21st November 2012) - Marteau, Clémentine; Nardello‐Rataj, Véronique; Favier, Dominique; Aubry, Jean‐Marie
ABSTRACT The antioxidant activity of 18 phenols, including standard antioxidants (e.g. butylated hydroxytoluene, α‐tocopherol) and fragrance molecules (e.g. eugenol, thymol) has been evaluated by measuring the rate constants for their reaction with the DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) radical in m‐xylene. Correlation with the bond dissociation energies supports the involvement of the hydrogen atom transfer mechanism. The radical trapping ability of α‐tocopherol, eugenol and isoeugenol has been investigated in five solvents of different polarity and in a series of homologous alcohols. In comparison to α‐tocopherol, the increase of the observed scavenging kinetics for eugenol and isoeugenol in alcohols suggests that the sequential proton loss electron transfer (SPLET) takes place. The addition of acetic acid eliminates the SPLET mechanism and confirms its predominance in polar solvent. The major effects of the pKa of fragrant phenols and of the solvent dielectric constant on the SPLET mechanism are discussed. Some fragrance phenols, such as mesitol and eugenol, show a significant reactivity towards the DPPH radical in m‐xylene, which is more pronounced for eugenol derivatives in alcohols. Copyright © 2012 John Wiley & Sons, Ltd.